Evaluation of Poultry Protein Isolate as a Food Ingredient: Physicochemical Properties and Sensory Characteristics of Marinated Chicken Breasts. Issue 7 (14th June 2013) - Khiari, Zied; Omana, Dileep A.; Pietrasik, Zeb; Betti, Mirko
Abstract: The possibilities of replacing soy protein isolate (SPI) and reducing the amount of phosphate in marinated chicken breasts using poultry protein isolate (PPI) were investigated. PPI, prepared from mechanically separated turkey meat through the pH‐shift technology, was used as a marinade ingredient for chicken breasts at 2 different concentrations (1.0% and 1.5%, w/w on a dry weight basis). Product characteristics were compared to samples marinated with salt, phosphate, or SPI. All the 5 treatments were subjected to instrumental and sensory analyses. Tumbling yield, drip, and cooking losses as well as expressible moisture showed that PPI can be used as a substitute for SPI in brine. The sensory analysis revealed that there were no differences among treatments in terms of appearance, color, flavor, saltiness, juiciness, tenderness, and overall acceptability of the marinated chicken breasts. However, chicken breasts marinated with phosphate had significantly higher aroma acceptability scores than those treated with 1% PPI.